Silicon Induces Heat and Salinity Tolerance in Wheat by Increasing Antioxidant Activities, Photosynthetic Activity, Nutrient Homeostasis, and Osmo-Protectant Synthesis - Ansa Aouz; Imran Khan; Muhammad Bilal Chattha; Shahbaz Ahmad; Muqarrab Ali; Iftikhar Ali; Abid Ali; Fatmah M. Alqahtani; Mohamed Hashem; Tasahil S. Albishi; Sameer H. Qari; Muhammad Umer Chatta; et al. (Plants, 2023)
Modern agriculture is facing the challenges of salinity and heat stresses, which pose a serious threat to crop productivity and global food security. Thus, it is necessary to develop the appropriate measures to minimize the impacts of these serious stresses on field crops. Silicon (Si) is the second most abundant element on earth and has been recognized as an important substance to mitigate the adverse effects of abiotic stresses. Thus, the present study determined the role of Si in mitigating adverse impacts of salinity stress (SS) and heat stress (HS) on wheat crop. This study examined response of different wheat genotypes, namely Akbar-2019, Subhani-2021, and Faisalabad-2008, under different treatments: control, SS (8 dSm−1), HS, SS + HS, control + Si, SS + Si, HS+ Si, and SS + HS+ Si. This study’s findings reveal that HS and SS caused a significant decrease in the growth and yield of wheat by increasing electrolyte leakage (EL), malondialdehyde (MDA), and hydrogen peroxide (H2O2) production; sodium (Na+) and chloride (Cl−) accumulation; and decreasing relative water content (RWC), chlorophyll and carotenoid content, total soluble proteins (TSP), and free amino acids (FAA), as well as nutrient uptake (potassium, K; calcium, Ca; and magnesium, Mg). However, Si application offsets the negative effects of both salinity and HS and improved the growth and yield of wheat by increasing chlorophyll and carotenoid contents, RWC, antioxidant activity, TSP, FAA accumulation, and nutrient uptake (Ca, K, and Mg); decreasing EL, electrolyte leakage, MDA, and H2O2; and restricting the uptake of Na+ and Cl−. Thus, the application of Si could be an important approach to improve wheat growth and yield under normal and combined saline and HS conditions by improving plant physiological functioning, antioxidant activities, nutrient homeostasis, and osmolyte accumulation.